2015
DOI: 10.3851/imp2988
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Herpes Simplex virus Activities of Bioactive Extracts from Antrodia Camphorata Mycelia

Abstract: A. camphorata mycelia and antrodin A might have potential use as anti-HSV agents and are promising candidates for future antiviral drug design.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 18 publications
0
8
0
Order By: Relevance
“…A subsequent study by the authors showed the extract elicits its effect early in the viral replication cycle by blocking HSV-2 attachment, adsorption, and entry into host cells. 191 Furthermore, He et al 39 observed an ethanolic extract of the fungus Antrodia camphorata to have antiviral activity against HSV-1 (strain F) and HSV-2 (strain G). Although not nearly as potent as acyclovir, A. camphorata was found to inhibit viral plaque formation with IC 50 values of 61.2 mg/ml and 57.5 mg/ml for HSV-1 and HSV-2, respectively.…”
Section: Asiamentioning
confidence: 99%
See 1 more Smart Citation
“…A subsequent study by the authors showed the extract elicits its effect early in the viral replication cycle by blocking HSV-2 attachment, adsorption, and entry into host cells. 191 Furthermore, He et al 39 observed an ethanolic extract of the fungus Antrodia camphorata to have antiviral activity against HSV-1 (strain F) and HSV-2 (strain G). Although not nearly as potent as acyclovir, A. camphorata was found to inhibit viral plaque formation with IC 50 values of 61.2 mg/ml and 57.5 mg/ml for HSV-1 and HSV-2, respectively.…”
Section: Asiamentioning
confidence: 99%
“…Furthermore, He et al 39 observed an ethanolic extract of the fungus Antrodia camphorata to have antiviral activity against HSV-1 (strain F) and HSV-2 (strain G). Although not nearly as potent as acyclovir, A. camphorata was found to inhibit viral plaque formation with IC 50 values of 61.2 μg/ml and 57.5 μg/ml for HSV-1 and HSV-2, respectively.…”
Section: Single Herbs In Vitromentioning
confidence: 99%
“…Recently, the crude ethanol extract of Antrodia camphorate has been found to have the potential to inhibit HSV-1. Whilst fraction A and B being the major fractions in the extract, fraction A exhibited better anti-HSV-1 activity than crude extract, suppressing HSV-1 replication significantly in Vero cells after being infected with HSV-1 for 1 to 4 h [ 34 ]. Besides, the dried seeds of N. nucifera were collected and their ethanolic extracts were identified as NN-H, NN-E, and NN-B.…”
Section: Natural Anti-hsv-1 Products From Tcmmentioning
confidence: 99%
“…Other natural products inhibit HSV-1 by impairing the replication of viral genes. Fraction A in the crude ethanol extract of Antrodia camphorate significantly suppressed HSV-1 replication in Vero cells after being infected with HSV-1 for 1 to 4 h [ 34 ]. Nevertheless, further studies are required to find out the molecular mechanism and signal pathway mining of compound A against HSV-1.…”
Section: The Pharmacodynamic Mechanism Of Tcm Against Hsv-1mentioning
confidence: 99%
“…cinnamomea. which possess anticancer and anti-inflammatory activities. In addition, a number of benzenoids in A. cinnamomea have been reported to possess anti-inflammatory activity.…”
Section: Introductionmentioning
confidence: 99%